Irek Mukhamedov's Spartacus Recent review - Kasner, Charlotte (Dance Books Ltd., Alton,Hampshire (UK), 2005)
PALABRAS CLAVE: Hong Kong Ballet, Spartacus, Irek Mukhamedov, Yuri Grigorovich.
Dentro del apartado "Dance Now. Recent Reviews".